(3GdfXQGJs - (3eSde Hf MehO GdMSjfj GdMdjs ((3SHW GdeDda(B: (3CSO Gddg GdMSjfj GdMdjs)
(3ChdgG (B:s
(3fXQI aj GdeGOI(B. (3Ch efGXQI eY GdeGOJjf(B. (3GdeGOI YfO GdbOeGA ef adGSaI GdjhfGf(B...s
(3BNQgG (B:s
(3hYQaJ GdeBNP hGdeMGPjQ Ydi ef GdJRe HGdeGOI HfbGT Ydej hMSGH(B... (3hgPG eG CQOfG EjQGOg(B...s
(3JHUQI GdYfhGf (B:s
(3GdefGXQGJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds